Five Hundred Patients With Gut Malrotation: Thirty Years of Experience With the Introduction of a New Surgical Procedure. Issue 4 (October 2021) - Abu-Elmagd, Kareem; Mazariegos, George; Armanyous, Sherif; Parekh, Neha; ElSherif, Ayat; Khanna, Ajai; Kosmach-Park, Beverly; D'Amico, Giuseppe; Fujiki, Masato; Osman, Mohammed; Scalish, Marissa; Pruchnicki, Amanda; et al.
Abstract : Objectives: Define clinical spectrum and long-term outcomes of gut malrotation. With new insights, an innovative procedure was introduced and predictive models were established. Methods: Over 30-years, 500 patients were managed at 2 institutions. Of these, 274 (55%) were children at time of diagnosis. At referral, 204 (41%) patients suffered midgut-loss and the remaining 296 (59%) had intact gut with a wide range of digestive symptoms. With midgut-loss, 189 (93%) patients underwent surgery with gut transplantation in 174 (92%) including 16 of 31 (16%) who had autologous gut reconstruction. Ladd's procedure was documented in 192 (38%) patients with recurrent or de novo volvulus in 41 (21%). For 80 patients with disabling gastrointestinal symptoms, gut malrotation correction (GMC) surgery "Kareem's procedure" was offered with completion of the 270° embryonic counterclockwise-rotation, reversal of vascular-inversion, and fixation of mesenteric-attachments. Concomitant colonic dysmotility was observed in 25 (31%) patients. Results: The cumulative risk of midgut-loss increased with volvulus, prematurity, gastroschisis, and intestinal atresia whereas reduced with Ladd's and increasing age. Transplant cumulative survival was 63% at 10-years and 54% at 20-years with best outcome among infants and liver-containing allografts. Autologous gut reconstruction achieved 78% and GMC had 100% 10-year survival. Ladd's was associated with 21% recurrent/de novo volvulus and worsening ( P > 0.05) of the preoperative National Institute of Health patient-reported outcomes measurement information system gastrointestinal symptom scales. GMC significantly ( P ⩽ 0.001) improved all of the symptomatology domains with no technical complications or development of volvulus. GMC improved quality of life with restored nutritional autonomy ( P < 0.0001) and daily activities ( P < 0.0001). Conclusions: Gut malrotation is a clinicopathologic syndrome affecting all ages. The introduced herein definitive correction procedure is safe, effective, and easy to perform. Accordingly, the current standard of care practice should be redefined in this orphan population. Abstract : Supplemental Digital Content is available in the text